Mycoplasmas as Host Pantropic and Specific Pathogens: Clinical Implications, Gene Transfer, Virulence Factors, and Future Perspectives - Dawood, Ali; Algharib, Samah Attia; Zhao, Gang; Zhu, Tingting; Qi, Mingpu; Delai, Kong; Hao, Zhiyu; Marawan, Marawan A.; Shirani, Ihsanullah; Guo, Aizhen (Frontiers in Cellular and Infection Microbiology, 2022)
Mycoplasmas as economically important and pantropic pathogens can cause similar clinical diseases in different hosts by eluding host defense and establishing their niches through their limited metabolic capacities and enormous undiscovered virulence. On the other hand, they are host-specific pathogens that can colonize a vast number of habitats by reshuffling their genetic information and evolving rapidly. However, currently, only a few control measures exist against some of mycoplasmosis which are far from satisfaction. This review aimed to provide an updated insight into the state of mycoplasmas as pathogens by summarizing and analyzing the comprehensive progress, current challenge, and future perspectives of mycoplasmas. It covers clinical implications of mycoplasmas in humans and domestic and wild animals, virulence-related factors, the process of gene transfer and its crucial prospects, the current application, and future perspectives of nanotechnology for diagnosing and curing mycoplasmosis, Mycoplasma vaccination, and protective immunity. Several questions remain unanswered and are recommended to pay close attention to. The findings would be helpful to develop new strategies of basic and applied research on mycoplasmas and facilitate the control of mycoplasmosis for humans and various species of animals.